2012
DOI: 10.1200/jco.2011.39.9394
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Regorafenib in Patients With Metastatic and/or Unresectable GI Stromal Tumor After Failure of Imatinib and Sunitinib: A Multicenter Phase II Trial

Abstract: Regorafenib has significant activity in patients with advanced GIST after failure of both imatinib and sunitinib. A phase III trial of regorafenib versus placebo is ongoing to define more fully the safety and efficacy of regorafenib in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
174
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(187 citation statements)
references
References 23 publications
8
174
0
3
Order By: Relevance
“…However, 16 of 25 of patients had been treated with more than two prior TKIs before study entry. The nine patients in our study who were treated with pazopanib as third-line therapy received a median of two cycles [1][2][3][4][5][6][7][8][9] which is comparable with nilotinib, but inferior to regorafenib [1][2][3]. The fact that our patients were heavily pretreated with multiple TKIs may have affected the outcome of this trial possibly due to multiple secondary mutations.…”
Section: Discussionmentioning
confidence: 99%
“…However, 16 of 25 of patients had been treated with more than two prior TKIs before study entry. The nine patients in our study who were treated with pazopanib as third-line therapy received a median of two cycles [1][2][3][4][5][6][7][8][9] which is comparable with nilotinib, but inferior to regorafenib [1][2][3]. The fact that our patients were heavily pretreated with multiple TKIs may have affected the outcome of this trial possibly due to multiple secondary mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical benefi t rate was 75% due to 4 PRs and 22 instances of SD more than 16 weeks; moreover, the median PFS was 10 months ( 89 ). Preclinical studies have suggested a potential role for FGF pathway activation in the resistance to imatinib ( 60 ).…”
Section: Overcoming Drug Resistancementioning
confidence: 99%
“…In a phase I/II study which had included a total of 97 metastatic, imatinib-resistant GISTs, of which 9 were wild-type GISTs, sunitinib was more active in KIT exon 9 mutant and wild-type GISTs than KIT exon 11 mutations (Heinrich et al 2008). In the group of treatment failures after imatinib and sunitinib, administration of regorafenib showed significant activity, with median PFS of 12 months (George et al 2012). Likewise, pazopanib demonstrated a potential response in heavily pretreated patients, though only five wild-type GIST patients were recruited in this phase II study .…”
Section: Carney-stratakis Syndromementioning
confidence: 99%